AB0621 Expression of Serum B Cell Activating Factor from the Tumor Necrosis Factor Family (BAFF) and of Proliferation-Inducing Ligand (APRIL) in Patients with Untreated Systemic Lupus Erythematosus. (9th June 2015) - Panafidina, T.; Sokhova, M.; Popkova, T.; Verizhnikova, Z.; Novikov, A.; Aleksandrova, E.; Solovyev, S.; Nasonov, E.
Abstract : Background: B lymphocyte stimulator signaling pathway by BAFF and its homologue APRIL has an important role in the selection, maturation and survival of B cells and plays a significant role in the pathogenesis of systemic lupus erythematosus (SLE). Objectives: The aim of this study is to determine serum levels of BAFF and APRIL in patients with untreated SLE, excluding the influence of the therapy. Methods: The study included 27 pts (81% females, age 30.0 [26.0-33.0] years (median [interquartile range 25%>75%]) with untreated SLE (ACR criteria, 1997) and 47 controls (96% females without any rheumatic and infectious diseases, age 31.0 [26.0-49.0] years). None of SLE pts was treated with either prednisone or cytotoxic drugs at the moment of the study, 3 (11%) pts received hydroxychloroquine 200 mg/day. SLE-related factors, including disease duration, clinical features, SLE Disease Activity Index (SLEDAI 2K) and Systemic Lupus International Collaborating Clinics (SLICC) damage index were evaluated in parallel with relevant laboratory findings (blood and urine tests, CRP, immunoglobulins G, A and M, complement C3 and C4 fragments and others), autoantibodies (ANA, antiDNA, ENA-SSA, -SSB, -Sm, -RNP-70, aPL) and CD19 B lymphocytes subpopulation count. Serum levels of BAFF and APRIL (ng/ml) were measured by ELISA (Bender MedSystem GmbH, Austria). B cells were detected by flow cytometry. Statistical analyses were performed with STATISTICA program, version 8.0. Results: Mean SLE duration was 1.0 [0.5-5.0] years, SLEDAI 2K score - 10 [7-19], SLICC damage index score - 0 [0-0]. SLE pts had higher levels of APRIL vs control (3.04 [2.01-4.05] vs 0.01 [0.01-4.36] ng/ml, p <0.05), with no difference in BAFF level (0.07 [0.01-0.69] vs 0.02 [0.01-0.03] ng/ml). In SLE pts serum APRIL level correlated with leucocytes (r=-0.47, p <0.05) and lymphocytes absolute counts (r=-0.77, p <0.01), creatinine level (r=0.61, p <0.001) and glomerular filtration rate (r=-0.67, p <0.001); BAFF level correlated with SLEDAI 2K (r=0.43, p <0.05), antiβ2-GP-1 IgM (r=-0.60, p <0.05), glomerular filtration rate (r=-0.42, p <0.05) and hemoglobin level (r=-0.40, p <0.05). We divided SLE pts on two groups: Group 1 included pts with lupus nephritis (n=16 (59%)), Group 2 – SLE pts without nephritis (n=11 (41%)). Pts from Group 1 had higher levels of BAFF as compared to Group 2 levels (0.5 [0.03-1.20] vs 0.01 [0.01-0.07] ng/ml, p <0.05) or control group levels (0.5 [0.03-1.20] vs 0.02 [0.01-0.03] ng/ml, p <0.05), with no difference in APRIL levels between the groups. Conclusions: Untreated SLE patients had high disease activity and increased serum levels of APRIL as compared to healthy control ( p <0.05). BAFF level was associated with disease activity. Patients with lupus nephritis had higher BAFF concentration as compared to control and SLE patients without nephritis. Disclosure of Interest: None declared